‘The soul has no disability’: inclusion of people with disabilities in rural South Africa - Nomvo Dwadwa-Henda; Gubela Mji; Chioma Ohajunwa (Rural and Remote Health, 2025)
Introduction: Persons with disabilities are often excluded and discriminated against in society. Current research has showed that it is within rural communities that persons with disabilities suffer the most exclusion due to myriad challenges. This article explores the role of spirituality informed by the indigenous concept of Ubuntu, in framing health and wellbeing of persons with disabilities within three South African rural communities. The study is based in South Africa's Eastern Cape, focusing on AmaBomvane - a subgroup of AmaXhosa, who still practice their indigenous customs and rituals. Presented this context are the experiences of persons with disabilities of Xhosa rituals and traditions from childhood to adulthood, and how these experiences contribute to their collective health and wellbeing. The concepts of Ubuntu, and the spirituality of Ubuntu, connote sharedness of spaces, discourses and practices that promote disability inclusion within these rural contexts, influencing how disability is understood by the community. Methods: A qualitative exploratory case study was used for the study, underpinned by critical ethnography. Purposive sampling and snowball sampling were used to select 50 participants. Seven focus groups and 11 in-depth interviews were conducted by the researcher and the research assistant, including observations and journalling, which were solely done by the researcher. Content analysis was used to analyse all the transcripts. Results: Four main themes emerged and are discussed in this article to demonstrate inclusion of persons with disabilities. These findings show that the Indigenous worldview of AmaBomvane facilitates inclusion and diversity, which influence their understanding of disability. Hence, disability is viewed as outside the person, for the person is regarded as a soul that has no disability. Conclusion: The Indigenous worldview of AmaBomvane influences cultural practices that shape the understanding of disability and informs an inclusive-disability approach that embraces humanity. The spirituality of humanity transcends a mundane understanding of disability as a deficit of the person.